KAJIAN PRODUKSI DAN PENDAPATAN USAHATANI KAKAO PADA PROGRAM GERNAS (GERAKAN NASIONAL) KAKAO DI SULAWESI TENGGARA - Finayah Akhirul; Taane La Ola; Azhar Bafadal; Budiyanto Budiyanto (Universitas Halu Oleo, 2018)
The study was conducted from January to December 2015 in Andomesinggo Village, Besulutu District, Konawe Regency and Lambandia Village, Lambandia District, East Kolaka Regency. The study aims to examine the production and income of cocoa farming after the GERNAS Kakao program has been implemented. Determination of respondents was carried out in census. Data collected were analyzed descriptive quantitatively. The results of the study show that GERNAS Kakao program has been able to significantly increase cocoa farming production. The average production of cocoa farming in Southeast Sulawesi in 2015 was 871.80 kg per ha while the average production of cocoa beans produced by farming in the GERNAS Kakao program was 1,000.78 kg per ha. The average cocoa farming income in the GERNAS Kakao program is Rp 35,920,865, - per ha.Keywords: production; income; GERNAS Kakao program